Local immunosuppression induced by high viral load of human papillomavirus: characterization of cellular phenotypes producing interleukin‐10 in cervical neoplastic lesions. Issue 1 (1st July 2015) - Prata, Thiago Theodoro Martins; Bonin, Camila Mareti; Ferreira, Alda Maria Teixeira; Padovani, Cacilda Tezelli Junqueira; Fernandes, Carlos Eurico dos Santos; Machado, Ana Paula; Tozetti, Inês Aparecida
Summary A specific immune response to human papillomavirus (HPV) in the cervical microenvironment plays a key role in eradicating infection and eliminating mutated cells. However, high‐risk HPVs modulate immune cells to create an immunosuppressive microenvironment, and induce these immune cells to produce interleukin 10 (IL‐10). This production of IL‐10, in conjunction with HPV infection, contributes to the appearance of cervical neoplastic lesions. We sought to characterize the IL‐10‐producing cellular phenotype, and investigate the influence of host and HPV factors upon the induction of an immunosuppressive microenvironment. Immunohistochemical analysis demonstrated an increase in IL‐10 production by keratinocytes, macrophages and Langerhans cells in high‐grade cervical lesions and cervical cancer. This increase was more pronounced in patients older than 30 years, and was also correlated with high viral load, and infection with a single HPV type, particularly high‐risk HPVs. Our results indicate the existence of a highly immunosuppressive microenvironment composed of different IL‐10‐producing cellular phenotypes in cervical cancer samples, and samples classified as high‐grade cervical lesions (cervical intraepithelial neoplasia stages II and III). The immunosuppressive microenvironment that developed for these different cellular phenotypes favours viral persistence and neoplastic progression.